Rus and Khazars - Howard-Johnston, James (Studia Ceranea, 2023)
The southern thrust of the Rus in the ninth–tenth centuries is to be explained not only by Viking hunger for wealth and glory, but also by the large, rapidly growing market for furs in the Caliphate. In order to reach that market, the Rus had to cross the Khazars’ sphere of influence in the steppes and wooded steppes of the Volga and Don regions. The khaganate was a great power, which presided over many client peoples. It was perhaps awareness of the potential threat posed by the Rus which prompted the Khazars to improve their northern defences in the 830s. There is clear evidence that they then extended their authority over the Rus, their khagan being acknowledged as Rus ruler. The subsequent history of the Rus, up to their successful rebellion in 965, can only be understood if account is taken of Khazar influence and of wider geopolitical circumstances. The following propositions, all to some extent conjectural, are put forward: (1) that the first Rus attack on Constantinople in 860 was a show of force, timed to coincide with several Arab raids on Byzantine territory, and that it was initiated by the Khazars at the urging of the central Abbasid authorities; (2) that Byzantium was seeking a useful ally both against the Balkan Bulgars and against the Sajids of Azerbaijan, when it offered substantial trade concessions to the Rus in 911, that no objection was made by the Khazars, who had recently faced problems from the Oghuz Turks and their Pecheneg clients, and that the treaty resulted in a damaging Rus raid in the Caspian region after 912–913; (3) that there was a serious deterioration in Khazar-Byzantine relations in the 920s; (4) that the second Rus attack on Constantinople in 941 (this time in great force) was instigated by the Khazars, in response to an abortive Rus rebellion; and (5) that the Rus subsequently patched up relations with the Khazars, who allowed them to invade Azerbaijan in 944–945, and made peace with the Byzantines, signing a new trade treaty in 944. Apart from some evidence of assimilation of Khazar customs, it was the division of the Rus into twenty or so distinct principalities which was the principal longterm outcome of Khazar influence.